The Effectiveness of Government Expenditure on Poverty: Evidence of Urban-Rural Spatial Heterogeneity in Indonesia - Fauzi Faisal Akbar (Public Policy and Management Inquiry, 2025)
This study aims to empirically analyze the effectiveness of local government expenditure across nine functional categories on poverty levels in Indonesia, highlighting spatial heterogeneity between urban and rural areas. The research employs panel data from 33 provinces over the 2015–2024 period (excluding DKI Jakarta as an outlier), sourced from the Directorate General of Fiscal Balance (DJPK) and Statistics Indonesia (BPS), analyzed using Random Effects GLS regression based on the Hausman test. The results reveal a very high rho value (0.956 in urban areas and 0.979 in rural areas), confirming the dominance of structural heterogeneity across provinces. In urban areas, public service and health expenditures proved most effective in reducing poverty, whereas economic and social protection expenditures showed a significant positive relationship with poverty, indicating targeting errors and a social protection trap phenomenon. In rural areas, health expenditure exerted twice the impact compared to urban areas, while tourism and cultural expenditure emerged as an effective inclusive fiscal instrument. The study concludes that the effectiveness of local expenditure is context-dependent and cannot be applied uniformly, requiring differentiated fiscal strategies between urban and rural regions to achieve more targeted poverty alleviation.